Drinking Water and Public Health in an Era of Aging Distribution Infrastructure. (October 2018) - Allen, Martin; Clark, Robert; Cotruvo, Joseph A.; Grigg, Neil
The provision of a safe and sustainable drinking water supply is one of the hallmarks of a successful society. Treated drinking water entering distribution systems in virtually all U.S. public drinking water systems meets regulations and is microbiologically safe. However, the opportunity for microbial contamination from decades to century old water distribution systems is increasing with time. Thus, increased health risk to consumers should be a driving factor in accelerating reinvestment in America's aging water distribution water systems.